2018
DOI: 10.1200/jco.2018.78.9602
|View full text |Cite
|
Sign up to set email alerts
|

Epacadostat Plus Pembrolizumab in Patients With Advanced Solid Tumors: Phase I Results From a Multicenter, Open-Label Phase I/II Trial (ECHO-202/KEYNOTE-037)

Abstract: PurposeTumors may evade immunosurveillance through upregulation of the indoleamine 2,3-dioxygenase 1 (IDO1) enzyme. Epacadostat is a potent and highly selective IDO1 enzyme inhibitor. The open-label phase I/II ECHO-202/KEYNOTE-037 trial evaluated epacadostat plus pembrolizumab, a programmed death protein 1 inhibitor, in patients with advanced solid tumors. Phase I results on maximum tolerated dose, safety, tolerability, preliminary antitumor activity, and pharmacokinetics are reported.Patients and MethodsPatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
208
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(210 citation statements)
references
References 30 publications
2
208
0
Order By: Relevance
“…In human patients, epacadostat monotherapy was not effective (163,164), while combined administration with PD-1 or cytotoxin T-lymphocyte-associated protein 4 (CTLA-4) inhibitors showed promising clinical activity in phase I/II studies (165)(166)(167)(168). Unfortunately, a recent trial with combined administration of epacadostat with pembrolizumab found no superiority over pembrolizumab alone (169).…”
Section: Immune Tolerance Related To Indoleamine 23-dioxygenase 1 Acmentioning
confidence: 99%
“…In human patients, epacadostat monotherapy was not effective (163,164), while combined administration with PD-1 or cytotoxin T-lymphocyte-associated protein 4 (CTLA-4) inhibitors showed promising clinical activity in phase I/II studies (165)(166)(167)(168). Unfortunately, a recent trial with combined administration of epacadostat with pembrolizumab found no superiority over pembrolizumab alone (169).…”
Section: Immune Tolerance Related To Indoleamine 23-dioxygenase 1 Acmentioning
confidence: 99%
“…13 The genetic differences between acral and mucosal melanomas and cutaneous melanomas may contribute to the IDO expression levels in tumors and in the peritumoral stroma. Although anti-PD-1 inhibitor/IDO-1 inhibitor combination therapy in phase I/II trials had encouraging antitumor activity in metastatic melanomas, 26 the results of the phase 3 study did not detect the efficacy of them. 27 Because our results showed the varying IDO expression profiles between major melanoma subtypes, anti-PD-1 inhibitor/IDO-1 inhibitor combination therapy targeted for specific strata of melanoma patients may merit consideration.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase I study, epacadostat monotherapy did not show any objective responses among patients with colon cancer, melanoma, or renal cell carcinoma . In a phase I/II study using epacadostat and pembrolizumab for solid cancers, the ORR for melanoma was 55% . Of the 2 patients with HNSCC, one achieved a partial response .…”
Section: Combination Therapy For Hnsccmentioning
confidence: 94%
“…In a phase I/II study using epacadostat and pembrolizumab for solid cancers, the ORR for melanoma was 55% . Of the 2 patients with HNSCC, one achieved a partial response . Two phase I/II trials used epacadostat with nivolumab and pembrolizumab in patients with HNSCC (Table ).…”
Section: Combination Therapy For Hnsccmentioning
confidence: 99%
See 1 more Smart Citation